Предмет: Математика,
автор: Анютоо4ка
5,6-3(2-0,4х)=0,4(4х+1)
Ответы
Автор ответа:
11
5,6-6+1,2х=1,6х+0,4
5,6-6-0,4=1,6х-1,2х
-0,8=0,4х
Х=-0,8:0,4
х=-2
Ответ:х=-2
5,6-6-0,4=1,6х-1,2х
-0,8=0,4х
Х=-0,8:0,4
х=-2
Ответ:х=-2
Анютоо4ка:
Спасибо большое !!
Автор ответа:
5
5,6-3(2-0,4х)=0,4(4х+1)
5,6-6+1,2х=1,6х+0,4
1,2х-1,6х=-5,6+6+0,4
-0,4х=0,8
х=0,8:(-0,4)
х=-2
Похожие вопросы
Предмет: Русский язык,
автор: inna75
Предмет: Английский язык,
автор: seadetibrahim
Предмет: Окружающий мир,
автор: stesha24
Предмет: Алгебра,
автор: ekaterinatihon67
Предмет: Математика,
автор: 9371188845df